2021
DOI: 10.1007/s10560-021-00774-9
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Sport-Based Positive Youth Development During the COVID-19 Pandemic

Abstract: Sport is a foundational context for social, emotional, physical, and psychological development. The COVID-19 pandemic displaced many youth from their normative sport activities. As a result, sport-based positive-youth development (PYD) programs, typically delivered in person, had to reimagine ways to reach and engage youth in sport and life skill development. In fall 2020, The Los Angeles Football Club Youth Leadership Program (LAFC YLP) developed seven virtual sport-based PYD videos and one workshop for 120 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 34 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…For example, a PYD program through basketball in the western region of the US showed that structured sports programs can promote positive character development, such as autonomy [16]. Bates, Greene, and O'Quinn [17] found that even virtual sports-based PYD programs in Los Angeles, CA during the COVID-19 pandemic were able to engage Latinx youth and their families, improving youths' life skills. Other research showed positive results of a sports youth development program for Latinx youth regarding significant improvement in social skills, school connectedness, and peer support [18].…”
Section: Positive Youth Developmentmentioning
confidence: 99%
“…For example, a PYD program through basketball in the western region of the US showed that structured sports programs can promote positive character development, such as autonomy [16]. Bates, Greene, and O'Quinn [17] found that even virtual sports-based PYD programs in Los Angeles, CA during the COVID-19 pandemic were able to engage Latinx youth and their families, improving youths' life skills. Other research showed positive results of a sports youth development program for Latinx youth regarding significant improvement in social skills, school connectedness, and peer support [18].…”
Section: Positive Youth Developmentmentioning
confidence: 99%
“…Examples of empirically supported PYD programs that can be conducted via online arrangements include Project PATHS (Shek & Sun, 2013), Big Brother/Big Sister School-based Mentoring (Hererra et al, 2011), and the Second Step Social-Emotional Learning Programme (Frey et al, 2005). Virtual sports (Bates et al, 2021) and leisure (Ettekal & Agans, 2020) activities also have the potential to promote PYD amid the ongoing pandemic and may be implemented alongside students' academic tasks. Providing real-life exercises beyond online interactions, such as maintaining meaningful conversations with parents, developing empathy with peers and recognising positive emotions, can also help students capitalise on their psychological strengths amid the challenges of current pandemic.…”
Section: Future Directions For Pyd Research and Practicementioning
confidence: 99%
“…This study’s relevance is further enhanced by the fact that it was conducted during the COVID-19 pandemic, thus revealing the possible impact of the pandemic on the expression of the skills under investigation. Due to COVID-19 restrictions, including the closures of schools, sport schools, parks, recreation centers, and the cancellation of youth sports, the “youth was at an increased risk for sedentary behaviors that influence their health, well-being, and academic performance.” [ 52 ] (p. 437), and a variety of social problems emerged. Apart from in-person sport activities, youths have fewer opportunities to build relationships and gain additional social support [ 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to COVID-19 restrictions, including the closures of schools, sport schools, parks, recreation centers, and the cancellation of youth sports, the “youth was at an increased risk for sedentary behaviors that influence their health, well-being, and academic performance.” [ 52 ] (p. 437), and a variety of social problems emerged. Apart from in-person sport activities, youths have fewer opportunities to build relationships and gain additional social support [ 52 ]. Changes in youth activities—especially in relation to activities with peers and other adults—have led to varying degrees of social isolation [ 53 ], and the social isolation experienced by many children had a significant impact on children’s positive behavioral skills [ 54 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation